2012 IEEE 23rd International Symposium on Personal, Indoor and Mobile Radio Communications - (PIMRC) 2012
DOI: 10.1109/pimrc.2012.6362732
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency analysis in relay assisted hybrid-ARQ communications

Abstract: Introduction 2 Motivations and system model 3 Related works and contributions 4 Theoretical energy efficiency in relay assisted network 5 Simulation results 6 Conclusions and future works M. Maaz Cooperative communications 2 / 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Pr [τ k1,k2 ], (18) where · is the rounding function (rounding to the next highest integer). In fact, (18) shows the outage probability of C-ARQ protocols with limited number of retransmissions (also known as the truncated retransmission).…”
Section: B Distribution Of τ and Outage Probability Of C-arqmentioning
confidence: 99%
See 2 more Smart Citations
“…Pr [τ k1,k2 ], (18) where · is the rounding function (rounding to the next highest integer). In fact, (18) shows the outage probability of C-ARQ protocols with limited number of retransmissions (also known as the truncated retransmission).…”
Section: B Distribution Of τ and Outage Probability Of C-arqmentioning
confidence: 99%
“…In fact, (18) shows the outage probability of C-ARQ protocols with limited number of retransmissions (also known as the truncated retransmission). We do not focus on the truncation of C-ARQ protocols in this work.…”
Section: B Distribution Of τ and Outage Probability Of C-arqmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works [15], [16], EE in relay-assisted HARQ scheme have been analyzed in a single user context without considering any resource optimization problem. In particular in [16], we have been interested in the EE analysis for HARQ schemes in single user source-relay-destination framework, when a practical FPGA target is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The error rate, delay, and EE for cooperative the HARQ-Chase combining (CC) protocol have been studied in [25]. In [26], the authors have shown that when considering the circuitry energy consumption, relaying deployments are not always energy efficient.…”
mentioning
confidence: 99%